Alienação parental e os impactos na formação escolar da criança - Pelim, Arlice Rodrigues (Brasil, 2023)
Our research entitled “Parental Alienation and the Impacts on the Education of the Child”, is an interdisciplinary investigation in which studies from areas such as Law, Psychology, Pedagogy and Psychopedagogy come together. Our main purpose is to investigate the pedagogical difficulties, almost always of an emotional-cognitive basis, presented by children in the early years who are facing disorders related to the Parental Alienation Syndrome (PAS). In this endeavor, it is necessary to know about the cognitive and affective dimensions that are present in the school learning process of the child affected by this dystopian phenomenon of contemporary society, increasingly common in Brazil and which unfortunately is also associated with the phenomenon of domestic violence, usually with women as the main target. Impacts that produce perverse effects on the school learning of children in the initial schooling process, in this case, in the first years of Elementary School. The theoretical-methodological course followed the clues of Edgar Morin's theory of complexity, putting opposing and complementary categories in motion and dialoguing, by valuing the emotional and cognitive plane of learning under conditions of simultaneity. The research sought to base its foundations on the psychology and psychiatry studies of the American Richard Alam Gardner (1931-2003). Keywords: Parental Alienation, Early Years, Domestic Violence, Emotional Learning.